2014
DOI: 10.1371/journal.pone.0084501
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Detection and Clinical Significance of ALK Rearrangement in Selected Advanced Non-Small Cell Lung Cancer: ALK Expression Provides Insights into ALK Targeted Therapy

Abstract: BackgroundThis study aimed to elucidate clinical significance of anaplastic lymphoma kinase (ALK) rearrangement in selected advanced non-small cell lung cancer (NSCLC), to compare the application of different ALK detection methods, and especially evaluate a possible association between ALK expression and clinical outcomes in crizotinib-treated patients.MethodsALK status was assessed by fluorescent in situ hybridization (FISH), immunohistochemistry (IHC) and quantitative RT-PCR (qRT-PCR) in 173 selected advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…This observation was consistent with another study, which showed that ALK-positive adenocarcinomas might metastasize to lymph nodes early, despite the small size of the primary tumor (Jokoji et al, 2010;Paik et al, 2012;Takamochi et al, 2013). To date, several small sample studies (Takahashi et al, 2010;Zhang et al, 2014;Toll and Maleki, 2015) have reported that ALK rearrangements were associated with moderate or poor differentiation status; our study further affirmed this finding in a relatively larger sample size.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation was consistent with another study, which showed that ALK-positive adenocarcinomas might metastasize to lymph nodes early, despite the small size of the primary tumor (Jokoji et al, 2010;Paik et al, 2012;Takamochi et al, 2013). To date, several small sample studies (Takahashi et al, 2010;Zhang et al, 2014;Toll and Maleki, 2015) have reported that ALK rearrangements were associated with moderate or poor differentiation status; our study further affirmed this finding in a relatively larger sample size.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014). In our study, young age, female gender, and never-smokers were significantly associated with ALK rearrangement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ALKþ translocation confers special clinicopathologic features to the NSCLC cancer sub-type: ALK þ NSCLC patients tend to be diagnosed with lung cancer at a younger age 14,15,19,21,40 , and have a higher risk of developing brain (and other) metastases than patients with other NSCLC sub-types 20,21,41,42 . Brain metastases are known to severely impact a patient's quality-of-life (physical, cognitive, and functional impairments) 24,31,33 , as well as to result in high healthcare resource utilization 37 and substantial clinical 43 , economic 27 , and caregiver 32 burden.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of recent progresses of chemotherapy and novel therapies, the prognosis of lung cancer remains poor mostly because patients were at advanced stages when diagnosed. Lack of adequate tumor biomarkers for early diagnosis and metastasis identification is still one of the most important challenges in lung cancer therapy [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%